2019
DOI: 10.1111/vsu.13217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings associated with development of postoperative reflux and short‐term survival after small intestinal surgery in geriatric and mature nongeriatric horses

Abstract: Objective To determine risk factors, especially age, associated with postoperative reflux (POR; >2 L of reflux present upon intubation), high‐volume POR (≥20 L in 24 hours), and short‐term outcome after small intestinal (SI) surgery. Study design Retrospective case‐control study. Sample population Horses aged ≥16 years (geriatric; range, 16–30; n = 44) and <16 years (mature; range, 2–15; n = 39) with an SI surgical lesion that survived general anesthesia and did not have a second exploratory celiotomy during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
(132 reference statements)
1
6
0
Order By: Relevance
“…Median rectal temperature was 38.0°C (IQR, 37.2‐38.3); fever (≥38.6°C) was identified in 5 cases. Median heart rate was 44 beats per minute (IQR, 39‐53 beats per minute); tachycardia (≥45 beats per minute) was recorded in 30% (19/52) of cases; and median respiratory rate was 20 breaths per minute (IQR, 14‐24 breaths per minute) …”
Section: Resultsmentioning
confidence: 99%
“…Median rectal temperature was 38.0°C (IQR, 37.2‐38.3); fever (≥38.6°C) was identified in 5 cases. Median heart rate was 44 beats per minute (IQR, 39‐53 beats per minute); tachycardia (≥45 beats per minute) was recorded in 30% (19/52) of cases; and median respiratory rate was 20 breaths per minute (IQR, 14‐24 breaths per minute) …”
Section: Resultsmentioning
confidence: 99%
“…The development of an incisional abscess is not unique to standing surgery and is also reported following ventral midline celiotomy (Rubio Martínez et al., 2012). The gelding also experienced postoperative ileus in the immediate period following the first surgery, but this was considered mild due to the short volume and duration and was successfully treated medically (Boorman et al., 2019). Despite this, the total treatment cost of the two standing procedures was less than that of a typical surgical small intestinal colic case performed under general anaesthesia at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…One study of horses with naturally-occurring colitis found the likelihood of non-survival increased by 11.8% for every year the horse aged, and that horses ≥ 20 years of age were 15.2 times more likely to die than young adults, independent of financial considerations, comorbidities, and duration of hospitalization [76]. In contrast, a study examining post-operative recovery from colic surgery in aged and adult horses found no differences in the severity of post-operative reflux or likelihood of survival [111]. Clearly much remains to be elucidated regarding the effect of age on disease in horses.…”
Section: Chronic Inflammatory Diseasesmentioning
confidence: 91%